Hepatitis B capsid as a delivery vehicle into mammalian cells - Lee, Khai Wooi (2012)
The recombinant hepatitis B virus (HBV) core antigen (HBcAg) expressed in Escherichia coli self-assembles into icosahedral virus-like particles (VLPs) of about 35 nm. It possesses a range of surface chemistries for recombinant DNA alteration and chemical modification to display cell-targeting signals on its surface. The HBcAg nanoparticles could serve as a potential nano-container to package therapeutic molecules for drug and gene delivery. In this study, the association,dissociation and the molecule packaging properties of the C-terminally truncated HBcAg (tHBcAg) were studied with protein denaturants. Light scattering analysis and transmission electron microscopy (TEM) revealed that the dissociated tHBcAg was able to re-associate into nanoparticles when the denaturants were removed. In order to evaluate the potential of the nanoparticles in capturing molecules, the green fluorescent protein (GFP) was used as a model for encapsidation. Data showed that the GFP molecules were packaged and remained active in the tHBcAg nanoparticles after the dissociation and re-association steps. The insertion of foreign peptides at the N-terminal end of HBcAg displays the inserts on the surface of the nanoparticles. In order to develop the tHBcAg nanoparticles as a cell specific delivery system, the HBV preS11-108 region was employed as a ligand to target the human hepatocytes. The preS11-108 region was fused to the N-terminal end of the His6HBcAg (preS1His6HBcAg) via recombinant DNA technique. However, the fusion protein was insoluble in E. coli and did not form VLPs. A method to reconstruct and to display the preS1 on the tHBcAg nanoparticle was established by dissociating an appropriate molar ratio of the tHBcAg to the preS1His6HBcAg in urea. Gold immuno-TEM showed that the subunit mixture reassembled into icosahedral nanoparticles, displaying the preS1 ligand on the surface of VLPs. In order to assess the application of the reconstructed VLPs (rVLPs) as a delivery vehicle, fluorescein molecules were cross-linked on the tHBcAg of the rVLPs and tested on hepatocytes in vitro. Fluorescence microscopy revealed that the fluorescent rVLPs were internalised into HepG2 cells, efficiently. The peptide, SLLGRMKGA has been shown to bind and chemically cross-link the aspartic acid residues (D64 and D78) or glutamic acid residue (E77) at the tips of tHBcAg nanoparticles. The following study reports an extension of this idea as a universal ‘nano-glue’ to display different cell-internalising peptide (CIP) at the tips of tHBcAg nanoparticles. As a model of our studies, peptide ligand that internalised HeLa cells were selected from a random 12-mers peptide library displayed on filamentous M13 phage. Immuno-fluorescence microscopy showed that the isolated M13 clones, displaying HTLQIPQHATSF, KLHISKDHIYPT and THASKNTSYFTV internalised HeLa cells specifically. The isolated peptide (KLHISKDHIYPT) was co-synthesised with the ‘nano-glue’ sequence (KLHISKDHIYPTGGGSLLGRMKGA; JG24) and conjugated chemically to the tHBcAg nanoparticles using cross-linkers (EDC and sulfo-NHS). Transmission electron microscopy (TEM) revealed that the tHBcAg nanoparticles remained intact after the conjugation. Interestingly, when the peptide was conjugated to the fluorescein labelled tHBcAg (FtHBcAg) nanoparticles, the nanoparticles internalised HeLa cells and the fluorescent was observed under a fluorescence microscope.tHBcAg nanoparticles were later used to packaged fluorescent oligonucleotide,conjugated with cell-targeting peptide and added to HeLa cells. Fluorescent microscopy revealed the delivery of the oligonucleotide into the cells. The tHBcAg nanoparticles could serve as a potential nano-vehicle to package molecules and to target various cells specifically by displaying different cell specific ligands at the N-terminal region or having the CIPs conjugated chemically at the tips of tHBcAg nanoparticles.